I'm having trouble manipulating the function of this series which has factorials to show that it converges or diverges using the ratio test.

The series is $\sum\limits_{k=1}^{\infty}\dfrac{(k!)^2}{(2k)!}$. The following are the steps I used, but I made a mistake expanding/canceling the factorial portion somewhere which I can't figure out..

First write the limit using ratio test: $$\lim\limits_{k\to\infty}\dfrac{((k+1)!)^2}{(2k+2)!}\cdot\dfrac{(2k)!}{(k!)^2}$$ Expand to cancel factorials: $$\lim\limits_{k\to\infty}\dfrac{((k+1)(k!))^2}{(2k+2)(2k+1){(2k)}!}\cdot\dfrac{(2k)!}{(k!)^2}$$

Then after canceling I got:


This would result in polynomials of the same degree in the numerator and denominator, and the coefficients of the $k^2$ term would be 1 and 4, so I said the series converges because $\dfrac{1}{4} < 1$ which means the series converges by the ratio test. However, the series is supposed to diverge according to my book. I don't have much practice working with factorials so I know my mistake must be somewhere in there. Any help is appreciated.

  • 4
    $\begingroup$ Your work is correct. Seemingly your text is incorrect. $\endgroup$ Apr 2, 2014 at 4:28
  • 3
    $\begingroup$ Wolfram Alpha confirms convergence: wolframalpha.com/input/…*+%28i%21%29%2F%282i%29%21 $\endgroup$
    – ml0105
    Apr 2, 2014 at 4:33
  • 1
    $\begingroup$ The work above is correct. The series is convergent. $\endgroup$
    – kmitov
    Apr 2, 2014 at 4:34
  • 1
    $\begingroup$ Yep, looks good to me as well. $\endgroup$
    – MPW
    Apr 2, 2014 at 4:39
  • 1
    $\begingroup$ $\binom{2k}{k}\sim\frac{4^k}{\sqrt{\pi k}}$. Thus, the terms of your series are $\sim\frac{\sqrt{\pi k}}{4^k}$ which shows why the ratio test gives $\frac14$. $\endgroup$
    – robjohn
    Apr 2, 2014 at 5:02

2 Answers 2


The series is supposed to diverge according to my book.

Unless that book is the Bible, I suggest you take any information contained therein with a grain of salt. :-) As already noted by the other commenters, the series converges, so you did alright. More to the point, its value is $\displaystyle\sum_{n=1}^\infty\frac1{2n\choose n}=\frac13+\frac{2\pi\sqrt3}{27}$ . We know this because of the more general result $$\sum_{n=1}^\infty\frac{(2x)^{2n}}{{2n\choose n}n^2}=2\arcsin^2x\quad\iff\quad\Big(1-x^2\Big)\cdot\sum_{n=0}^\infty\frac{(2x)^{2n}}{2n\choose n}=1+\frac{x}{\sqrt{1-x^2}}\arcsin x,$$ $\quad$ which can be deduced by integrating the binomial series expansion of $\dfrac1{\sqrt{1-x^2}}=\arcsin'x$.


For integers $1 \leq j \leq k,$ we find $(j + k) \geq 2 j.$ As a result, $$ \frac{(k!)^2}{(2k)!} = \prod_{j=1}^k \frac{j}{j+k} \leq \prod_{j=1}^k \frac{1}{2} = \frac{1}{2^k} $$

Detail, $$ \frac{j+k}{j} = 1 + \frac{k}{j} \geq 1 + 1 = 2, $$ so $$ \frac{j}{j+k} \leq \frac{1}{2} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.